Impact of integrating disaster risk reduction philosophies into infrastructure reconstruction projects in Sri Lanka - Palliyaguru, Roshani; Amaratunga, Dilanthi; Haigh, Richard (Journal of Civil Engineering and Management, 2012)
Major impacts on infrastructures due to natural and man-made hazards could result in secondary and additional impacts, compounding the problem for those communities already affected by the hazard. Integration of disaster risk reduction (DRR) philosophies into infrastructure projects has been an important solution to mitigate and prevent such disaster risks, as well as for a speedy recovery after disasters. “Vulnerability reduction” is defined by the research community as an enabler which facilitates the process of DRR. However, there is a research need to identify the most beneficial DRR strategies that would result in vulnerability reduction in an effective way. As part of this main aim, this paper seeks to explore the nature of various vulnerabilities within infrastructure reconstruction projects and their respective communities and to evaluate the DRR practises within these projects. Finally the paper attempts to map the effects of integration of DRR into infrastructure reconstruction on vulnerability reduction of infrastructure reconstruction projects and the communities which benefited from such projects. This study adopts the case study approach and the paper is entirely based on data collated from semi-structured interviews and a questionnaire survey conducted within one case study (a water supply and sanitation reconstruction project) in Sri Lanka and expert interviews conducted in Sri Lanka and the United Kingdom. Results reveal that emergency preparedness strategies are the most important group of DRR strategies, while physical/technical strategies are also very important. However, none of the emergency preparedness strategies are satisfactorily implemented, while most of the physical/technical strategies are adequately implemented.